LOCAL WISDOM FOR THE DEVELOPMENT OF SANGKAN GUNUNG RURAL TOURISM - Ginaya, Gede; Zuraidah, Zuraidah; Pugra, I Wayan (International Conference on Cultural Studies, 2019)
Bali is one of the tourist destinations in Indonesia that has been widely known in the world. In 2017, Bali was awarded as the world's best travel destination by TripAdvisor, the world's largest travel site. The award also impacted the increase of government efforts to achieve a target of 20 million foreign tourists in 2019. In fact, this award and a number of other awards that have been pinned on this island of the gods was achieved because the unity of implementation of the values of Tri Hita Karana (THK) and Sad Kertih (SK) as local wisdom in maintaining balance Bali. However, tourism development is now focused only on economic growth with the development of mass tourism, so that tourists become difficult to find the uniqueness of Bali because they do not find enough information The truth about Bali.   This research aims to investigate the revitalization of the values of THK and SK in the development of the tourism village of Sangkan Gunung, Sidemen subdistrict, Karangasem regency. The methods used are qualitative descriptive with participatory observation, in-depth interviews, and document studies. While the theory used is the theory of hermeneutics and phenomenology the results showed that the need for revitalization, transformation, conservation, and re-actualization of local wisdom values of THK and SK, as an attempt to realize the multiplier Effects of the development of a community-driven tourism village and based on the values of local wisdom that ultimately comes down to the welfare of society that is balanced between birth and inner.